The effectiveness of different education methods conducted at different times for decreasing the time required for a parturient to position herself for epidural placement - Chen Yang; Yan Cheng; Jianying Hu; Yaojun Lu; Xinhua Yu; Shaoqiang Huang (BMC, 2022)
Abstract Background Decreasing the anaesthesia preparation time for primiparas experiencing painful uterine contractions is clinically relevant. This prospective intervention study investigated the effect of various educational methods conducted at different times on body positioning for primiparas undergoing labour analgesia. Methods Ninety primiparas who were about to receive labour analgesia were randomly divided into a verbal instruction group, a photo instructions group, and an educational video group for immediate education, and 60 primiparas who were willing to receive labour analgesia but were not in labour were randomly divided into a photo instruction group and an educational video group for advance education. The times required for body positioning were compared. Results In the immediate education cohort, the body positioning time in the verbal group (50.48 ± 28.97 s) was significantly longer than those in the photo group (30.47 ± 6.94 s) and the video group (23.14 ± 9.74 s) (P = 0.00). In the advance education cohort, the time in the photo group (17.47 ± 6.48 s) was longer than that in the video group (13.71 ± 7.01 s) (P = 0.042). Whether photos or videos are used, advance education can significantly decrease body positioning time. Conclusions Video or photo education for primiparas who are about to receive labour analgesia can decrease the body positioning time and is more effective when provided in advance.